2023
DOI: 10.1186/s13256-023-04000-1
|View full text |Cite
|
Sign up to set email alerts
|

Legionella associated rhabdomyolysis: a case report

Abstract: Background Infections have been recognized as an uncommon cause of rhabdomyolysis, with evidence indicating a worse prognosis when compared to rhabdomyolysis caused by other etiologies. Diseases caused by Legionella pneumophila can present variably, ranging from mild to severe illness, as is sometimes the case with pneumonia. In particular, the triad of Legionnaire’s disease, rhabdomyolysis, and acute kidney injury is associated with a significant increase in the morbidity and mortality, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Legionnaires' disease must be diagnosed correctly as it can have a fatality rate of 10% if left untreated [ 1 ]. In a retrospective study, Heath et al reported that delaying antibiotic initiation after hospital admission and symptom onset were factors related to higher mortality in Legionella pneumophila (L. pneumophila) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Legionnaires' disease must be diagnosed correctly as it can have a fatality rate of 10% if left untreated [ 1 ]. In a retrospective study, Heath et al reported that delaying antibiotic initiation after hospital admission and symptom onset were factors related to higher mortality in Legionella pneumophila (L. pneumophila) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%